Pengaruh Audio Visual terhadap Kemampuan Berbahasa Anak - Soemarmi, Soemarmi; Hariyani, Indaria Tri; Eriyani, Neneng (Universitas Negeri Padang, 2024)
The appropriate time in developing the basic abilities and potention of children is in the first five years of childhood which known as the golden age. Both physical motoric ability, language, cognitive, and social emotional. In this research, the basic abilities of children which is expanded is language. Therefore the writer is trying to have research on efforts to improve the development preteen language with audio visual media. This research involves the proteges at at-Taqwa Babatan Mukti kindergarten, Surabaya. Based on recent surveys, the language development of the research subject has not developed optimally. The purpose of this research is to know how audio visual affects to the language capabilities and know children’s interest in audio-visual learning. The method used by the writer in this research is quantitative descriptive method. As a field research, that is a study about audio visual effect in developing children’s language. After a series of research carried out from May 11- May 18 2023. In the early observation the subject had not shown good results yet in audio visual media learning. Related to language skill. But after a series of treatment for the subject we have, it is indicated that the protege has reached the criteria for success. The results show that language development in children from A group of AT-TAQWA kindergarten Wiyung Surabaya is making progress. This is indicated by the presentation from children’s activation result in pre-test by 68,75% undergoes progress in post test by 87,50% and the presentation of children’s language abilities result in pre-test by 50% undergoes progress in post test by 75,80%.